Pengaruh Disiplin dan Motivasi terhadap Kinerja Pegawai pada Badan Pengelola Pajak dan Retribusi Daerah (BPPRD) Kota Jambi - Desita Aliana (Universitas Batanghari Jambi, 2021)
Humane resource management is a process that consists of planning, organizing, leaders andcontrolling activities related to job analysis, job evaluation, procurement, development, compensation, promotion, and termination of employment in order to achieve the stated objectives. The method used in this research is the study of literature’s, a study conducted by using literature and writer’s that is closely related to the object of study, which is intended to obtain studid. Besides theory and information sourced from the internet. BPPRD is one of the Regional Work Units covered by the Jambi City Government which was formed based on Jambi City Regional Regulation Number 14 of 2016 concerning the Establishment and Composition of Regional XDevices of Jambi City and JambiH Mayor Regulation Number 60 of 2016 concerning Position, Organizational Structure, Tasks,e and Functions and Work Procedures at the Jambi City BPPRD. Based on the results of the regression analysis it was concluded that the regression equation Y = 12559,175 + 5.284X1 + 7.165X2 + e, with R square 0.888. simultaneously has a rsignificant positive influence between discipline and motivation on the performance of employees with a significant value of 0,000. While quantitatively there is an influence of discipline on employee performance with a significant value of 0.68 and rmotivation towards employee performance with a significant value of 0.003. Because in this study discipline and motivation have a significant effect simultaneously on employee performance. Then it must be more attention and improved again, so that discipline and motivation on employee performance can be better in the future.